Pemetaan Sebaran dan Arah Aliran Lindi Menggunakan Metode Self Potential (SP) di Kali Kampung Bima Kefamenanu - Maneno, Regolinda; Dety Lestari, Anastasia Kadek; Kristoforus Fallo (Program Studi Fisika - Universitas San Pedro, 2026)
Leachate pollution is a common environmental issue in areas with open waste disposal activities, particularly along riverbanks. Kali Kampung Bima in Kefamenanu City is characterized by domestic waste accumulation that has the potential to generate leachate and contaminate the surrounding environment. This study aims to identify variations in natural subsurface potential values and to determine the migration pattern and flow direction of leachate in the waste accumulation zone of Kali Kampung Bima using the Self Potential (SP) method, a passive geophysical technique that measures natural electrical potential differences in the subsurface. Data acquisition was conducted using the fixed-base technique along two parallel survey lines, accompanied by daily and loop corrections to ensure data stability. The results show potential values ranging from positive to negative. Significant negative anomalies on line P (–15.97 to –17.36 mV) indicate electrokinetic processes associated with leachate migration toward the river channel, whereas line Q exhibits smaller and relatively homogeneous potential values, suggesting lower contamination intensity. The isopotential contour map reveals a leachate migration pattern from the waste accumulation area toward surface water flow. These findings demonstrate that the Self Potential method is effective for identifying negative anomalies related to leachate distribution and flow direction, and it provides a scientific basis for environmental pollution mitigation and sustainable waste management.